The Dietary Flavonoid, Luteolin, Negatively Affects Neuronal Differentiation - Swaminathan, Amrutha; Basu, Moumita; Bekri, Abdelhamid; Drapeau, Pierre; Kundu, Tapas K. (Frontiers in Molecular Neuroscience, 2019)
Luteolin, a polyphenolic plant flavonoid, has been attributed with numerous beneficial properties like anti-cancer, antioxidant and anti-inflammatory action. Luteolin has been reported earlier to be neuroprotective in models of spinal cord injury and traumatic brain injury and also induces neurite outgrowth in PC12 cells. However, the effect of luteolin on early differentiation, which might be important for its beneficial effects, is unknown. In this report, we show that luteolin negatively affected early differentiation of embryonic stem cells, hampering the formation of embryoid bodies. At later stages of differentiation, luteolin specifically inhibited neuronal differentiation, where the number of cells expression of early neuronal markers were suppressed, whereas luteolin treatment did not inhibit expressions of meso- and endodermal markers. Further, in a developing zebrafish model, luteolin treatment led to fewer numbers of mitotic cells in the brain. These specific effects of luteolin on neuronal differentiation could be due to its ability to inhibit the lysine acetyltransferase, p300 since the structurally closely related p300 non-inhibitor flavonoid, apigenin, does not inhibit neuronal differentiation. These results show that luteolin perturbs neuronal differentiation of embryonic stem cells.